Beyond numbers: the role of mathematics self-concept and spatial anxiety in shaping mental rotation performance and STEM preferences in primary education - Lennon-Maslin, Michelle; Quaiser-Pohl, Claudia; Wickord, Lea-Christin (Frontiers in Education, 2024)
Introduction Factors such as low self-concept and anxiety have been shown to negatively impact mathematical achievement and spatial skills, as well as enjoyment of math-related subjects. Understanding these factors is crucial for promoting STEM interest and performance, particularly among primary school students. Methods This cross-sectional study examines the influence of gender, childhood development stage, maths self-concept, spatial anxiety, perceived difficulty, mental rotation performance, and STEM preferences in a sample of 144 primary school students (mean age M = 8.47), comprising 70 girls and 74 boys. Data were collected through four questionnaires and a computerized Mental Rotation Task (MRT). Results Girls and tweens (9-to-11-year-olds) exhibit lower maths self-concept, impacting their preference for maths as a STEM subject. Girls also demonstrate higher spatial anxiety and perceived difficulty of the MRT compared to boys. Maths self-concept is significantly associated with spatial anxiety and perceived difficulty, while gender is not. Maths self-concept shows marginal effects on students’ accuracy on the MRT, with evidence of a mediating effect of spatial anxiety. Discussion These findings underscore the importance of maths self-concept in shaping STEM preferences, particularly among girls and tweens. Additionally, maths self-concept serves as a mitigating factor for spatial anxiety and perceived difficulty in spatial tasks among primary school children. The study also suggests that spatial anxiety may contribute to gender disparities in mathematics and STEM-related domains. Further research is needed to explore interventions targeting maths self-concept and spatial anxiety to promote equitable STEM engagement amongst primary school students.